2002
DOI: 10.1016/s0038-1098(02)00210-7
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric and first principles study of AlnC− clusters

Abstract: We study the carbon-dope aluminum clusters by using time-of-flight mass spectrum experiments and ab initio calculations. Mass abundance distributions are obtained for anionic aluminum and aluminum-carbon mixed clusters. Besides the well-known magic aluminum clusters such as Al In recent years, clusters and cluster-based materials have been a field of intensive research due to both fundamental and technological importance 1-7 . The structural, electronic, magnetic, and optical properties of the clusters are dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…During the survey of the binding affinity of Al n – with various organic molecules (pentane, ethanol, acetone, ...) to find suitable protecting ligands, we serendipitously found that carbon-containing aluminum clusters Al n C 1 – and Al n C 2 – were generated as the main reaction products. Although the formation of Al n C 1 – and Al n C 2 – in the gas phase has been reported previously, the structural information is limited to Al n C 1 – . , The mass peaks for Al 7 C 1 – and Al 24 C 1 – showed high abundances in a series of Al n C 1 – . It was proposed that the C atom is surrounded by Al atoms for n = 5–13 by theoretical calculations . The present study investigated the geometric and electronic structures of Al n C 2 – using photoelectron spectroscopy and density functional theory (DFT) calculation.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…During the survey of the binding affinity of Al n – with various organic molecules (pentane, ethanol, acetone, ...) to find suitable protecting ligands, we serendipitously found that carbon-containing aluminum clusters Al n C 1 – and Al n C 2 – were generated as the main reaction products. Although the formation of Al n C 1 – and Al n C 2 – in the gas phase has been reported previously, the structural information is limited to Al n C 1 – . , The mass peaks for Al 7 C 1 – and Al 24 C 1 – showed high abundances in a series of Al n C 1 – . It was proposed that the C atom is surrounded by Al atoms for n = 5–13 by theoretical calculations . The present study investigated the geometric and electronic structures of Al n C 2 – using photoelectron spectroscopy and density functional theory (DFT) calculation.…”
Section: Introductionmentioning
confidence: 74%
“…Two categories of structures were searched: the structures in which two carbons are bonded and those in which two carbons are dissociated. To construct the initial structures for Al n C 2 – , we first obtained optimized structures of pure Al cluster anions Al n – ( n = 5–13) and single-carbon-containing Al cluster anions Al n C 1 – ( n = 5–13) by referring to the structures reported previously. Stable structures in the former category were searched by optimizing the initial structures constructed by placing the C 2 unit at various positions of the optimized Al n – or by replacing one of the Al atoms of the optimized Al n +1 – with the C 2 unit.…”
Section: Methodsmentioning
confidence: 99%
“…The model was further extended to the description of Al n N species. [26][27][28][29][30] Several mechanisms can be found whereby closed shell species might be bound together to provide a stable Al 14 I 3 − cluster: Al 13 − -AlI 3 ͑equivalent to the AlI 4 − analog described above, isomer A͒; Al 13 I 2 − -AlI ͑similar to isomer B, as described above͒; Al 13 − -AlI-I 2 ͑isomer C͒; Al 13 I-I − -AlI ͑again, isomer B͒, and an isomer D. Clearly, one shortcoming of the compound jellium model in this case is the sheer number of logically consistent combinations of closed shell species that lead to a molecule. As shown in Fig.…”
Section: B Al 14 I X −mentioning
confidence: 99%
“…A series of small aluminum–carbon clusters have been investigated using anion photoelectron spectroscopy and theoretical calculations, and it was found that the Al 4 C – anion has a planar tetracoordinate carbon (ptC) structure with D 4h symmetry . In addition to the ptC structures, aluminum–carbon clusters were predicted to form many interesting structures such as planar pentacoordinate carbon structures, starlike structures, or carbon endohedral stable structures. In this work, we investigated the structures and chemical bonding of Al 4 C 6 –/0 clusters employing mass-selected anion photoelectron spectroscopy and first-principles theoretical calculations. Interestingly, it is found that the Al 4 C 6 – anion has a bowl-shaped distorted triangular structure and neutral Al 4 C 6 has a D 3h symmetry planar triangle-shaped structure.…”
Section: Introductionmentioning
confidence: 99%